2015
DOI: 10.1007/s00508-015-0742-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum antioxidant enzymes activities and oxidative stress levels in patients with acute ischemic stroke: influence on neurological status and outcome

Abstract: Our study demonstrated that acute ischemic stroke patients have increased oxidative stress and decreased antioxidant enzymes activities. These findings indicated that an imbalance of oxidant and antioxidant status might play a role in the pathogenesis of acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…The increase in SOD activity after 1 week corresponds with the results of the present study for HS patients (32). Milanlioglu et al (29) found similar results to that of the present study; no significant differences in serum GPx was found between stroke patients and healthy controls. Demirkaya et al (2001) found that red blood cell GPx activity decreased in the first 24 hours after the onset of stroke symptoms as compared with the control group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The increase in SOD activity after 1 week corresponds with the results of the present study for HS patients (32). Milanlioglu et al (29) found similar results to that of the present study; no significant differences in serum GPx was found between stroke patients and healthy controls. Demirkaya et al (2001) found that red blood cell GPx activity decreased in the first 24 hours after the onset of stroke symptoms as compared with the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Hydrogen peroxide is, in turn, trapped by CAT and GPx and converted to H 2 O and O 2 molecules. The balance between oxidative and antioxidant mechanisms of these enzymes is a critical component in cells against nerve damage associated with oxidative stress (29). Antioxidant enzymes in the plasma and red blood cells are the most important factors preventing oxidative damage caused by neurological diseases such as stroke (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, the relation between CoQ 10 and inflammation and oxidative stress has been reported in cell and animal models. Glial fibrillary acidic protein (GFAP), MDA, and superoxide dismutase (SOD) activity are important biomarkers in oxidative stress and neuroinflammatory processes after stroke, and they can predict functional outcomes [134][135][136]. In a short RCT, 60 patients with acute ischemic stroke were randomly assigned to a placebo or CoQ 10 -supplemented group (300 mg/day) for 4 weeks.…”
Section: Coq 10 and Ischemic Strokementioning
confidence: 99%
“…Increased oxidative stress and decreased antioxidant enzymes activity may play a role in the pathogenesis of both ischemic stroke and hemorrhagic stroke (30,31). The management of oxidative stress also showed promising results with significant improvement of long-term neurological function (32).…”
Section: Shared Pathophysiological Mechanismsmentioning
confidence: 99%